The Worldwide Diffusion of Market-Oriented Infrastructure Reform, 1977–1999 - Henisz, Witold J.; Zelner, Bennet A.; Guillén, Mauro F. (American Sociological Review, 2005)
Why do countries differ so much in the extent to which they adopt neoliberal, marketoriented reform in their infrastructure industries? Building on world-society and neoinstitutional theories in sociology, this paper argues that international pressures of coercion, normative emulation, and competitive mimicry strongly influence the domestic adoption of market-oriented reform. The paper considers the effect of such pressures on the adoption of four reform elements: the privatization of state-owned firms, the formal separation of the regulatory authority from the executive branch, the de facto elimination of executive political influence on the regulatory authority, and the opening of the retail market to multiple service providers. It finds generally robust support for its arguments using a multivariate probit analysis of reform adoption in the telecommunications and electricity industries of as many as 71 countries and territories between 1977 and 1999. The results also suggest that the coercive effect of lending by the IMF and World Bank differs for each reform element. The paper discusses the possibility that, by leading countries to adopt some reform elements but not others, international coercion may not produce ideal outcomes.